Dualism, Duality and the Complexity of Economic Institutions - William A. Jackson (International Journal of Social Economics, 1999)
Dualism - the division of an object of study into separate, paired elements - is widespread in economic and social theorising: key examples are the divisions between agency and structure, the individual and society, mind and body, values and facts, and knowledge and practice. In recent years, dualism has been criticised as exaggerating conceptual divisions and promoting an oversimplified, reductive outlook. A possible alternative to dualism is the notion of duality, whereby the two elements are interdependent and no longer separate or opposed, although they remain conceptually distinct. This paper argues that duality, if handled carefully, can provide a superior framework to dualism for dealing with the complexity of economic and social institutions.
Keywords: A12; B41; B52; Z13; 330; dualism; duality; complexity; institutions; economic theory